Teaching Conflict Resolution in the Bioecological System: Implementing Winning Colors®. (August 2017) - Clapper, Timothy C.; Rice, Donna M.
Purpose. The purpose of this article is to propose a solution forconflict resolution in abioecological system . Background. In 1979, Bronfenbrenner introduced hisbioecological theory of human development which suggested that children are immersed in four integrated systems that affect studentbehavior and success in public schools. More than thirty years later, thebioecological system has experienced several changes, most notably in the structure of the family and changes in the culture.Conflict can lead to tragedy but intervention programs have seen some success when any one of the four systems is positively affected.Winning Colors® can be an effective tool to teachconflict resolution andcommunication leading tosituational leadership, team building, conflict resolution, and improvedcommunication in any inter-personal situation.Winning Colors® uses four color cards with correspondingbehavior strengths that can be understood by children and adults in a short period. Aim. In this article, we explain howWinning Colors® program that has been used to teachconflict resolution and communication to thousands of learners. Conclusion. Winning Colors® can be implemented to teach conflict resolution and communication across the bioecological system.